Divergence in children’s gender stereotypes and motivation across STEM fields - Allison Master; Andrew N. Meltzoff; Daijiazi Tang; Sapna Cheryan (Proceedings of the National Academy of Sciences, 2025)
STEM disciplines are traditionally stereotyped as being for men and boys. However, in two preregistered studies of Grades 1 to 12 students in the United States ( N = 2,765), we find a significant divergence in students’ gender stereotypes about different STEM fields. Gender stereotypes about computer science and engineering more strongly favored boys than did gender stereotypes about math and science. These patterns hold across genders, intersections of gender and race/ethnicity, and two geographical regions. This divergence between different STEM fields was evident, although smaller, for children in elementary school compared to adolescents (students in middle school and high school). The divergence in stereotypes predicted students’ divergence in motivation for entering these fields. Gender stereotypes on average slightly favored girls in math and were egalitarian or slightly favored girls in science, while boys remained strongly favored for computer science and engineering, with implications for educational equity and targeted interventions.